Note regarding ticket prices
C03-0011-001 6d. - 1/- Prices - Top Gallery (Free) Balcony (Free) Grand Tier Boxes 4 Loggia Tier Boxes -1/ 6 (...) 1/- Stalls 1/- Lower orchestra Upper Orchestra 6d Free 292C/946/3/11